Sonographic and Pathologic Image Analysis of Pure Mucinous Carcinoma of the Breast - Kaoku, Setsuko; Konishi, Eiichi; Fujimoto, Yasuhisa; Tohno, Eriko; Shiina, Tsuyoshi; Kondo, Kengo; Yamazaki, Sanae; Kajihara, Mariko; Shinkura, Nobuhiko; Yanagisawa, Akio (Ultrasound in Medicine & Biology, 2013)
The aims of this study were to elucidate sonographic and histologic features of pure mucinous carcinoma (P-MC) of the breast using quantitative analysis and to evaluate the relationship between quantitative analysis and visual qualitative assessment. Eleven P-MCs (nine patients) were evaluated qualitatively and quantitatively. Three experts assessed these sonographic images using the Breast Imaging Reporting and Data System (BI-RADS) lexicon. For assessment of internal echoes and posterior echoes, quantitative measures were determined using ImageJ software. Histologic thin sections were stained for classification into separate parts of the tumor (stroma, mucin and cancer cells) and were digitized. Internal echoes were isoechoic in 7 of 11 (63.6%) tumors and hypoechoic in 4 of 11 (36.4%); all P-MCs were “enhanced” in qualitative evaluation. As internal echoes increased, the proportion of stroma increased and that of mucin decreased. The high level of internal echoes is correlated with reflection and back-scattering, which are caused mainly by the interface between mucin and stroma.